Efeketivitas Konseling Individu dalam Menurunkan Kejenuhan Belajar Siswa - Imami, Ainul; Karamoy, Yurike Kinanthy; Nur Budiono, Arifin (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
Learning is a process of behavior change. In the process prone to saturation. This happened to students in class XI Science 3 SMA Negeri 3 Jember still experiencing high learning saturation. This is obtained from the results of interviews and questionnaires. Many things can cause learning saturation, one of which is boredom that occurs over a long period of time and with a fairly high intensity, which is characterized by physical, mental, and emotional fatigue, as well as low self-esteem, which causes a person to feel distant from his environment. This study aims to reduce student learning saturation using individual counseling services. The type of research used is experimental design. Data collection techniques using questionnaires with a sample method in the form of purposive sampling. After individual counseling services with the SFBC approach with the call question technique on besline 2 decreased. The results of the study on besline I showed a score of 153, which was included in the high category, with a range of 136-180, while after the service was provided on besline 2 the score was medium, with a range of 91-130, or low, with a range of 45-90 Keywords: Burnout learning;Individual Counseling;SFBC